The drama searches on the fields of the "philosophy of the absurd": the experience of modern understanding - E. V. Myropolska, (Ukrainian Cultural Studies, 2020)
The article reflects the logics of the development of the "philosophy of absurd" – a term of intellectual tradition connected with attributive characteristic of reference between a man and surrounding world. The best productive ideas of the "philosophy of absurd" – non- conformism,resistance to the imposition of other people's thoughts, revolt, freedomand some others have been described.The "philosophy of absurd" is aphilosophical conception which examines a man in the context of his inevitable relations with the world which is sencseless and unfriendly to human individuality, in the result of which "absurd consciousness" is bearing. The nuances of the "philosophy of absurd" in the art practices of the XX-th – the first two decades of the XXI-st centuries, especially absurd drama has been disclosed. Its typical signs are the absence of act's plays and time, the plot and composition are breaking, existentialist's mood of characters, absurd plot's situations, words' nonsense and so on.The heroes of the plays by S. Becket from the very beginning are solitude. But S. Becket developes ideas of "the philosophy of absurd", showing that if such people find faith, there is no strength that can break them. The main theme of S. Becket's creation is man's doom, his solitude. S.Becket became the most typical interpretator of the ideas of "the philosophy of absurd" in the drama, finding both simple and non-traditional methodsfor classic theatre aesthetics and new means of their incarnation.The playwright very exactly expressed such thought: progress's movement causes "progress" to all mankind reticence, alienation, closeness. One of the reasons of the negative perception of the world S. Becket calls a man's unrealizness and as a result – man's deformation.The consciousness wich is prepared by philosophical comprehension and scene "playing" absurd situations, helps a modern man worthly treat such situations in the real life, understanding that life occurs Hic et Nunc, we can't delay it for tomorrow.
Keywords: philosophy of absurd, aesthetics, art practices, absurd drama